Pemanfaatan Model ISO 9126 Dalam Pengukuran Kualitas Perangkat Lunak Sistem Pengolahan E-Surat - Andy Rachman; Hendra Thesna Prayoga; Sulistyowati Sulistyowati (JURIKOM (Jurnal Riset Komputer), 2022)
The development of information technology impacts the use of technology in all fields and the many applications created to support the performance of companies, schools and even MSMEs. Today's very high-end app creation is not accompanied by good-quality support. Good software quality is one of the factors determining a software's success. The software created must be tested for software quality to reduce the loss of software procurement costs, time, and resources. To obtain good software quality, developers must carry out extra activities and a long process by implementing the ISO 9126 model. Six factors are used to determine software quality: functionality, reliability, usability, efficiency, portability, and portability. Keluarahan Sambikerep, Kecamatan Sambikerep, Surabaya, East Java, has developed an E-Letter application to serve the public in administrative activities. Still, the E-Letter application has not been tested for software quality. Researchers conduct quality testing of E-Letter software to ensure that the application complies with International Standards for software quality. By knowing the quality of the E-Letter software, it will automatically have an impact on the services provided by Kelurahan. Researchers use three factors from ISO 9126: functionality, usability, and efficiency. Researchers used black box testing with the equivalence partitions technique to test the E-Letter software. Researchers conducted 30 black box tests on the E-Letter application feature, namely the Login feature, citizen data submission form, birth certificate submission form, death certificate application form, citizen data report form, birth certificate report form, and death report form. From the ISO 9126 Implementation Process for the E-Letter application, an average rating of 81,667% or rounded up to 82% is obtained, which means that the E-Letter application has outstanding quality